Teachers' evaluation of professional development in support of national reforms - Gökmenoğlu, Tuba; Clark, Christopher M (Issues in educational research, 2015)
As in many other nations, the Turkish education system has undergone many significant curricular and structural reforms in the last decade. This study was designed to learn from teachers about the quality of professional development programs that were designed to support national reforms. It was based on a national survey of 1,730 Turkish teachers conducted in Spring 2012. The target population comprised K-8 teachers who were Classroom teachers (primary grades), or Mathematics, Science and Technology, Social Studies, Turkish, or English teachers in public schools in Turkey. Ten years into a period of intensive national reform, teachers reported that professional development activities only moderately satisfied them. The authors speculate that 'reform fatigue' may be partially responsible for relatively low teacher enthusiasm for mandatory, centrally designed training. Failure to adjust teacher development designs to meet established teacher preferences could undermine ambitious and expensive programs of national education reform. [Author abstract, ed]